The Est-hetics of Esthetics: Pedagogy as a Science of Life - Giuseppe Tognon (Firenze University Press, 2015)
The Est-hetics of educating is not a new "special field" in philosophy, but an attempt to move away from the pedagogic experience of art towards a philosophy of experience that surpasses the limitations of a paideia entirely centred on the tenet of what man ought to be. The study of the concept of beauty, from the kalokagatia of the ancient Greeks, to the crisis of esthetic formalism in the 20th century, help us to understand that, to make pedagogy a science of life, it is necessary to move away from the discon- nect between form and content and think again about the dialectic between critical thinking and that awareness of reality and beauty which is as much a part of our daily life as breathing.